Malignant peripheral nerve sheath tumor of thigh with sphenoid and brain metastases: Extremely rare occurrence with dismal prognosis despite significant response to palliative chemoradiotherapy - Purkayastha, Abhishek; Singh, Sankalp; Kapoor, Amul; Bhatia, Jasvinder Kaur; Bisht, Niharika; Husain, Azhar (World Journal of Nuclear Medicine, 2019)
Malignant peripheral nerve sheath tumor (MPNST) is a neurogenic tumor arising from peripheral nerves or nerve sheaths. MPNSTs are highly aggressive sarcomas mainly associated with neurofibromatosis type-1 (NF-1) with high rates of local recurrence and distant metastasis carrying a dismal prognosis. Lung is the most common metastatic site. Bone metastasis although documented in the literature is still very rare, while dissemination to brain without the involvement of lungs and that too in a non-NF-1 case is extremely unusual. A 48-year-old female was diagnosed with a case of non-NF-1 MPNST left thigh with bone metastases including sphenoid. Despite showing complete resolution of skeletal and primary lesions postpalliative chemoradiotherapy, she developed brain metastases and succumbed to her disease. This case is discussed to highlight an unusual scenario we encountered, the clinical course of the disease with its management, and overall poor prognosis. To the best of our knowledge, this may be the earliest case of MPNST with sphenoid metastases detected by 18-fluorodeoxyglucose positron-emission computed tomography scan and a sporadic case of brain metastases reported in the world literature.
Keywords: 18-Fluorodeoxyglucose positron-emission computed tomography scan; brain; chemoradiotherapy; malignant peripheral nerve sheath tumor; metastases; sphenoid